Biomethane Production Plants: a Case Study Aimed at Atex Zones Classification - Roberto Lauri (Chemical Engineering Transactions)
Biomethane is the purified version of biogas and it is one of the main renewable gases of the future and available to help decarbonise the European Union (EU) energy system. For these reasons, there is a clear need to increase the biomethane production by 2030, as reported in the RepowerEU (18 May 2022). In particular, the european biomethane production needs to reach 35 billion m3 by 2030. The strategic biomethane importance requires a specific attention to the production plants safety. Indeed, one of the main hazards associated with its production process is the possible formation of potentially explosive atmospheres (Atex zones) due to accidental releases from several components, such as valves, flanges, compressors, etc. In accordance with Atex Directive 99/92/EC, the employer is obliged to classify the workplaces zones, where explosive mixtures could occur. The paper is focused on a biomethane production plant and the goal is the classification of Atex zone, which could be generated by a potential biofuel release from the compressor. In particular, the biofuel compression unit has been examined, because it is the potentially more hazardous place. This hazardousness is due to the exiguous dilution of the natural ventilation (indoor place) and to the maximum biomethane pressure, which strongly increases the released mass flow. In the paper, a specific software has been used to study the biofuel outflow from the potential emission source (compressor) and classify the zone (hazardous or non-hazardous area).